Blink reflex monitoring in microvascular decompression for trigeminal neuralgia. (3rd July 2021) - Ying, Tingting; Bao, Bei; Yuan, Yan; Zhong, Wenxiang; Zhu, Jin; Tang, Yinda; Li, Shiting
ABSTRACT: Aim : To determine the value of the blink reflex in evaluating trigeminal sensory function during microvascular decompression for trigeminal neuralgia. Methods : The blink reflex (BR) in 103 patients with primary typical trigeminal neuralgia treated by microvascular decompression (MVD) was tested pre- and intraoperatively. The changes in BR were recorded. All patients underwent general anesthesia with intravenous propofol and fentanyl. Surgical efficacy and complications were evaluated after surgery. The relationship between intraoperative changes in the BR and postoperative trigeminal sensory function was analyzed. Results : The BR was elicited in all patients before surgery, and no significant difference was found between the affected side and the contralateral side. In 93 of the 103 cases, the BR was successfully elicited during MVD surgery. Therefore, the recordability of the BR was 90.29%. R1 latency on the affected side and the contralateral side were 11.62 ± 4.96 ms and 11.66 ± 4.37 ms, respectively. During MVD surgery, R1 of the BR disappeared on the affected side in 7 cases and remained in 86 cases. After the operation, 98 of the 103 patients had immediate and complete remission of trigeminal neuralgia symptoms, and 5 cases had partial remission. The 7 patients whose R1 disappeared during the surgery all experienced facial numbness postoperatively. Of the 86 patients whose R1 remained, only 2 patients had postoperative facial numbness. Of the 10 patients whose R1 was not recordable during the operation, one complained of postoperative facial numbness. No patients had complications such as facial paralysis, cerebrospinal fluid leakage, and death. Conclusions : Conclusion: The blink reflex may allow monitoring of trigeminal sensory function during microvascular decompression under general anesthesia.